Extending Research on Neighborhoods and Crime: An Examination of Mortgage Fraud across Chicago Census Tracts - Ranson, J.W. Andrew (Journal of quantitative criminology, 2019)
The purpose of this study is to extend research on communities and crime by assessing neighborhood variation in mortgage fraud.